Neurodevelopmental evaluation and referral practices in children with congenital heart disease in central South Africa - Smith, R.; Nel, H.; Marais, C.; Kraaij, R.; Le Roux, H.; Scholtz, E.; Steenkamp, R.; Van Eeden, T.; Van Wyk, M.; Van Rooyen, C.; et al. (SA Heart Journal, 2019)
Introduction: Children with congenital heart disease (CHD) are at higher risk for developmental delays than the general population. The American Heart Association (AHA) published a guideline to address these concerns in 2012. This study determined the neurodevelopmental evaluation and referral practices of practitioners in central South Africa. Method: An online survey was administered to practitioners (n=45) including paediatric cardiologists (n=4), cardiothoracic surgeons (n=4) and general paediatricians (n=37). Information on practitioner characteristics, awareness of the 2012 AHA guideline; and neurodevelopmental evaluation and referral practices was collected. Results: Twenty-one practitioners responded, including paediatric cardiologists (n=4), cardiothoracic surgeons (n=2) and paediatricians (n=15). Data for 20 practitioners was included. Despite most practitioners (n=18) indicating guidelines for the management of development were important, the majority (n=16; 80%) were unaware of the guideline. Most practitioners (n=18; 90%) failed to risk stratify children to identify those to be evaluated. Children with developmental delays were referred for formal developmental evaluation (n=11; 55%) and to intervention therapies (n= 15; 75%). Conclusion: Most practitioners are unaware of the 2012 AHA guideline. Awareness of the developmental risks associated with CHD and implementation of the guideline could promote early identification of developmental delays with referral to intervention therapies.